2021
DOI: 10.1111/jcmm.16568
|View full text |Cite
|
Sign up to set email alerts
|

Targeting LIMK1 with luteolin inhibits the growth of lung cancer in vitro and in vivo

Abstract: Lung cancer is the leading cause of cancer‐related deaths. LIM domain kinase (LIMK) 1 is a member of serine/threonine kinase family and highly expressed in various cancers. Luteolin, a polyphenolic plant flavonoid, has been reported to suppress tumour proliferation through inducing apoptosis and autophagy via MAPK activation in glioma. However, the mechanism of luteolin on suppressing lung cancer growth is still unclear. We found that luteolin targeted LIMK1 from the in silico screening and significantly inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 34 publications
1
23
0
Order By: Relevance
“…LIMK1 and LIMK2 exhibit the same domain architecture and have overlapping substrate specificities. While targeting LIMK1 has been used in vivo in cancer ( Zhang et al, 2021 ) and AD mouse models ( Henderson et al, 2019 ), LIMK2 functionality is essential for proper functionality of the eye ( Rice et al, 2012 ) and in spermatogenesis ( Takahashi et al, 2002 ). Thus, a specific LIMK1 isoform inhibition is desirable.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…LIMK1 and LIMK2 exhibit the same domain architecture and have overlapping substrate specificities. While targeting LIMK1 has been used in vivo in cancer ( Zhang et al, 2021 ) and AD mouse models ( Henderson et al, 2019 ), LIMK2 functionality is essential for proper functionality of the eye ( Rice et al, 2012 ) and in spermatogenesis ( Takahashi et al, 2002 ). Thus, a specific LIMK1 isoform inhibition is desirable.…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, overexpression of LIMK1 in breast cancer cell lines MCF-7 and MDA-MB-231 increased their motility, while inhibition of LIMK1 attenuated this effect ( Yoshioka et al, 2003 ). Targeting LIMK1 in lung cancer cells inhibits cell proliferation and induces apoptosis ( Zhang et al, 2021 ). Thus, LIMK1 is a promising drug target, potentially for a range of diseases.…”
Section: Introductionmentioning
confidence: 99%
“…For example, LUT suppresses the viability of RPMI-8226 multiple myeloma cells by enhancing the expression of cleaved caspase 3 and microtubule-associated protein light chain 3 (LC3)-II/I ( Chen et al, 2018 ). LUT also inhibits xenograft tumor growth by reducing Ki-67, p-LIMK, and p-cofilin expression ( Zhang et al, 2021 ). Furthermore, salvianolic acid inhibits tumor cell proliferation.…”
Section: Antitumor Activities Of S Miltiorrhizamentioning
confidence: 99%
“…Studies have indicated that other components of S. miltiorrhiza also block the cell cycle at different phases in various tumors cells. For example, LUT inhibits cell proliferation of bladder cancer and lung cancer through arresting the cell cycle in the G2/M phase and G1 phase, respectively ( Iida et al, 2020 ; Zhang et al, 2021 ). LUT blocks the cell cycle in the G2/M phase through upregulating p21 Waf1/Cip1 and p27 Kip1 as well as downregulating cyclin A and D1 in bladder cancer T24 cells ( Iida et al, 2020 ).…”
Section: Antitumor Activities Of S Miltiorrhizamentioning
confidence: 99%
“…Luteolin inhibited anchorage-independent colony growth and promoted cell cycle arrest at the G1 phase, apoptosis in lung cancer cells through regulation of peIF2α/CHOP and JNK pathway in a time-dependent manner. Further, luteolin also showed an increase in beclin-independent non-canonical autophagy mechanism accompanied by the suppression of LIM kinase-1 and related signalling pathway (p-LIMK1, p-cofilin and Ki-67) [ 72 , 73 ]. LIMK1, together with the downstream effector’s cofilin and Ki-67, is involved in the tumour cell filopodia formation resulting in migration, invasion, and metastasis [ 74 ].…”
Section: Roles Of Polyphenols In Autophagic Adaptation For Healthy Agingmentioning
confidence: 99%